The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00590-015-1614-5
|View full text |Cite
|
Sign up to set email alerts
|

The distinct prediction standards for radiological assessments associated with soft tissue injuries in the acute tibial plateau fracture

Abstract: The goal of this study was to assess the incidence of soft tissue injury in the tibial plateau fracture by magnetic resonance image (MRI) and reveal the relationship between the articular widening/depression and the risk of meniscus and ligament disorder. A total of 54 patients with tibial plateau fracture were indicated for operative intervention. Soft tissue injuries were assessed by MRI. Meniscus, anterior/posterior cruciate ligaments and medial/lateral collateral ligaments injuries on MRI were evaluated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…While many surgeons use a subjective assessment of widening when indicating patients for surgical treatment, a threshold LPW >5 mm has also been proposed in the literature (Honkonen, ; Parkkinen et al, ). This value was established through studies demonstrating associated soft tissue injuries at this threshold, but clear outcomes data on the amount of acceptable widening have yet to be established (Gardner et al, ; Durakbasa et al, ; Wang et al, ). Our results are also directly applicable to the intra‐operative assessment of reduction quality in tibial plateau fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many surgeons use a subjective assessment of widening when indicating patients for surgical treatment, a threshold LPW >5 mm has also been proposed in the literature (Honkonen, ; Parkkinen et al, ). This value was established through studies demonstrating associated soft tissue injuries at this threshold, but clear outcomes data on the amount of acceptable widening have yet to be established (Gardner et al, ; Durakbasa et al, ; Wang et al, ). Our results are also directly applicable to the intra‐operative assessment of reduction quality in tibial plateau fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Durakbasa et al () demonstrated that a preoperative LPW >10 mm was predictive of lateral meniscal injury through intraoperative direct visualization. Wang et al () were unable to predict soft tissue injury on the basis of tibial plateau widening. The variation noted in this study could explain the discrepancy in results among earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported correlations between radiological assessments and soft-tissue injuries in lateral tibial plateau fractures 11 14 , 24 . Gardner et al .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high-energy shearing and compressive stress exerted on the knee joint, menisci and ligaments are at considerable risk for injury, the overall incidence of which has been reported to be 39% to 99% and 16.7% to 57%, respectively 1 , 3 10 . Several authors have reported that soft tissue injury occurred more frequently with increasing displacement of tibial plateau fractures 11 14 . However, previous retrospective studies relied on data mostly obtained from MR images or arthroscopic findings.…”
Section: Introductionmentioning
confidence: 99%
“…Poor functional outcomes and a high incidence of meniscal pathology have led many authors to suggest a condylar width increase of >5 mm and varus/valgus instability >5° as an indication for surgery [38,72,79]. However, Wang et al [87] were unable to predict soft tissue injury based on tibial plateau widening. Johannsen et al [14] suggest that discrepancies in the literature on condylar widening can be reconciled by instead using a ratio of the articular widths of the femur and tibia in order to minimize problems in measurement with magnification and calibration.…”
Section: Surgical Indicationsmentioning
confidence: 99%